Alcohol consumption induces global gene expression changes in VTA dopaminergic neurons. (28th December 2015) - Marballi, K.; Genabai, N. K.; Blednov, Y. A.; Harris, R. A.; Ponomarev, I.
Abstract : Alcoholism is associated with dysregulation in the neural circuitry that mediates motivated and goal‐directed behaviors. The dopaminergic (DA) connection between the ventral tegmental area (VTA) and the nucleus accumbens is viewed as a critical component of the neurocircuitry mediating alcohol's rewarding and behavioral effects. We sought to determine the effects of binge alcohol drinking on global gene expression in VTA DA neurons. Alcohol‐preferring C57BL/6J × FVB/NJ F1 hybrid female mice were exposed to a modified drinking in the dark (DID) procedure for 3 weeks, while control animals had access to water only. Global gene expression of laser‐captured tyrosine hydroxylase (TH)‐positive VTA DA neurons was measured using microarrays. A total of 644 transcripts were differentially expressed between the drinking and nondrinking mice, and 930 transcripts correlated with alcohol intake during the last 2 days of drinking in the alcohol group. Bioinformatics analysis of alcohol‐responsive genes identified molecular pathways and networks perturbed in DA neurons by alcohol consumption, which included neuroimmune and epigenetic functions, alcohol metabolism and brain disorders. The majority of genes with high and specific expression in DA neurons were downregulated by or negatively correlated with alcohol consumption, suggesting a decreased activity of DA neurons in high drinking animals. These changes in the DA transcriptome provide a foundation for alcohol‐induced neuroadaptations that may play a crucial role in the transition to addiction. Abstract : Alcohol consumption induces global gene expression changes in VTA dopaminergic neurons.